Furuncular myiasis of the foot caused by the tumbu fly, Cordylobia anthropophaga: report in a medical student returning from a medical mission trip to Tanzania - Palmieri, James R (Dove Medical Press, 2013)
Cutaneous myiasis in humans is a temporary parasitic infestation of the skin by fly larvae or maggots of a variety of Dipteran families. In the United States, autochthonous cases of myiasis are infrequently seen. Most cases of cutaneous myiasis are acquired when traveling to tropical areas of Africa, Central America or South America. This case report involves a 26-year-old male medical student who visited Tanzania on a medical mission trip. Three weeks following his return to the United States he developed a furuncular lesion on the side of the fifth digit on his right foot, which contained the larva of the tumbu fly, Cordylobia anthropophaga.